Contributions of Rural Higher Education experiences from Colombia, Brazil and Mexico to the construction of a curriculum proposal in South Tolima (Colombia) - Laura Valentina Amado Ochoa; Laura Marcela García Salamanca; Jorge Jairo Posada Escobar; Luisa Fernanda Ramirez Cuervo (Universidade Federal do Norte do Tocantins, 2021)
This article presents a documentary study that aims to recognize the principles, curricular proposals and methodological strategies of the experiences of rural higher education in Colombia, Brazil and Mexico in the last 10 years. The analysis of the experiences makes it possible to generate contributions for a region of central Colombia, since the study is carried out within the framework of the research "Participatory construction of a curricular program of rural higher education based on agroecology as an alternative to territorial development in the pos -agreement". These experiences analysed are based on the recognition of peasants and indigenous peoples as cultural subjects, on the need for training for social transformation, the articulation of technical training components with the political and ecological aspects. The experiences propose contextualized curricula, with methodological and experiential strategies that start from peasant and indigenous knowledge, with the work of productive projects, community service and research.